The Effect of Civic Education Teacher Professionalism Citizenship Education Teacher Professionalism on Student Learning Achievement - Yaaman Giawa; Amstrong Harefa; Hendrikus Otniel Nasozaro Harefa; Estian Gulo; Lies Nofiyanti Gea (Universitas Muhammadiyah Enrekang, 2023)
Teacher professionalism has a strategic position in the success of student learning achievement. The research objectives are to obtain data, find out how much influence, find out whether there is an influence of civic education teacher professionalism on student learning achievement. The research method is a descriptive method with a quantitative approach, the population is class VIII students of SMP Negeri 1 Boronadu totaling 116, a sample of 22% of 116 as many as 25 people. The instrument is a closed questionnaire of teacher professionalism and learning achievement. Variable reliability test (X) output =0.752 and =0.396, then (0.752) > (0.396) output reliable. Variable (Y) (0.669)> (0.396) output valid. Reliability test of variable (X) =0.785 and =0.396 output reliable and variable (Y) is =0.836 and =0.396 output reliable. The output correlation coefficient test is 0.831 classified as high. The coefficient of determination test is 69 percent. Hypothesis testing = 7.165 and = 1.714 significant level of 0.05 or 5%, in the sense that the hypothesis Ha data is accepted.